1986
DOI: 10.2527/jas1986.632492x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Energy Source on Nutrient Digestibility in the Young Pig

Abstract: Dried whole whey, lard or dried skim milk was added to a corn-soybean meal basal diet to determine the effect on apparent nitrogen (ND), energy (ED) and dry matter digestibility (DMD) in pigs weaned at 28 d. Four groups of four littermate barrows were allotted to the experimental diets and placed in individual metabolism pens for 12 d (3 d adjustment and three collection periods of 3 d each) after weaning. The study was a 4 X 3 factorial with diet and period as main effects. Addition of dried skim milk or drie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 2 publications
1
7
0
2
Order By: Relevance
“…However, few researchers have attempted to determine the reason(s) why early weaned pigs respond to the inclusion of dried whey in the diet. Owsley et al (1986a) found that a diet containing 20% dried whey was higher in DM and energy digestibility than a corn-soybean meal diet for pigs weaned at 28 d. , Lindemann et al (1986) and Owsley et al (1986b) also reported that pigs fed diets containing dried whey had higher chymotrypsin, amylase, protease and lactase activity in the small intestine than did pigs fed a corn-soybean meal diet. Giesting et al (1985) indicated that the carbohydrate and protein fractions of skim milk hadan additive effect on the performance of starter pigs; however, such research has not been done with dried whey.…”
Section: Introductionmentioning
confidence: 89%
“…However, few researchers have attempted to determine the reason(s) why early weaned pigs respond to the inclusion of dried whey in the diet. Owsley et al (1986a) found that a diet containing 20% dried whey was higher in DM and energy digestibility than a corn-soybean meal diet for pigs weaned at 28 d. , Lindemann et al (1986) and Owsley et al (1986b) also reported that pigs fed diets containing dried whey had higher chymotrypsin, amylase, protease and lactase activity in the small intestine than did pigs fed a corn-soybean meal diet. Giesting et al (1985) indicated that the carbohydrate and protein fractions of skim milk hadan additive effect on the performance of starter pigs; however, such research has not been done with dried whey.…”
Section: Introductionmentioning
confidence: 89%
“…Uma das possíveis explicações para a melhora da CA pode ser o fato de o intestino dos leitões jovens não conseguir adaptar o transporte dos monossacarídeos aos desafios qualitativos e quantitatiTabela 2 -Efeito dos níveis de lactose da dieta sobre o desempenho de leitões desmamados aos 21 dias de idade Tabela 3 -Efeito dos níveis de lactose da dieta sobre o peso médio dos leitões em diferentes períodos vos da dieta e, portanto, poder processar apenas quantidades limitadas de produtos não-lácteos (VEGA et al, 1992). A superioridade da lactose sobre outras fontes de carboidratos para leitões desmamados precocemente (23 dias de idade) tem sido relatada também por outros pesquisadores, os quais relataram efeitos positivos sobre o desempenho (LEPINE et al, 1991;MAHAN, 1992;MAHAN, 1993;MAHAN e NEWTON, 1993;e NESSMITH et al, 1997a) e a digestibilidade da energia e dos nutrientes da dieta (OWSLEY et al, 1986;TURLINGTON et al, 1989;BERTOL e LUDKE, 1999). Após o desmame, ocorre aumento acentuado na atividade total das enzimas maltase e glicoamilase, induzido provavelmente pela presença do substrato e, também, por uma resposta adaptativa intrínseca, independente do consumo de alimento (KELLY et al, 1991).…”
Section: Resultsunclassified
“…The characteristical feature of weaning stress is also a rapid decline of pancreatic enzymes activity (Lindemann et al, 1986;Owsley et al, 1986) resulting in a significant reduction of apparent nutrient digestibility within the first week after weaning (Owsley et al, 1986;Le Dividich and Seve, 2000). There are also a qualitative changes in the composition of pancreatic juice.…”
Section: Modifications Of the Piglets Small Intestine Structure Durinmentioning
confidence: 99%